Factors influencing instruction competencies as perceived by technical and vocational education and training students in Malaysia - Lam, Kim Wai; Hassan, Aminuddin (Human Resource Management Academic Research Society, 2020)
The purpose of the study was to identify and describe factors influencing instruction competencies as perceived by Technical and Vocational Education and Training (TVET) students in Malaysia. The study described the students’ self-perceived level of knowledge and their perceived importance of instruction competencies for TVET courses conducted by a private vocational college in Kuala Lumpur and a public institution in Selangor. The study employed a mixed-method explanatory sequential study design. Data were gathered from a sample of 171 TVET students using the Instruction Competency Questionnaire (ICS). Descriptive statistics and Spearman correlation were used to analyses the data. This was followed by individual semi-structured interviews with 3 TVET students from the Selangor public institution. Feedback from the respondents of the ICS showed that 68.4% indicated that they had knowledge on scientific, interpretative, and critical paradigms. Significant correlations (p < .05) were reported (a) between perceived knowledge of experience in designing instruction and perceived knowledge of need for further education in instruction competence, and (b) between perceived importance of training on designing instruction and perceived importance of the need for further education in instruction competence. The study also showed that perceived importance of instruction competencies and perceived knowledge of instruction competencies were predictors for the need for further education on instruction competencies. The findings indicated that instruction competence was important for the overall quality of educational experience since it was shaped by expectations about the educational outcomes that students should manifest upon their graduation.